2007
DOI: 10.1111/j.1439-0434.2007.01268.x
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Phenols in the Resistance of Theobroma cacao against Phytophthora megakarya, the Causal Agent of Black Pod Disease

Abstract: The black pod disease caused by Phytophthora megakarya is responsible for 80% of the cocoa production loss in Cameroon. To assess the resistance of cocoa plants against this pathogen, necrotic lesions, phenolic content and qualitative alteration of phenolics were conducted in ICS84 and ICS95 clones (two Trinitario introduced from Trinidad) and their hybrids (families F30 and F25) derived from reciprocal cross breeding between these two parental clones after inoculation. The existence of strong hybrid vigour ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
20
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 16 publications
(22 reference statements)
8
20
0
1
Order By: Relevance
“…Among these flavonoids, flavan-3-ol units are a major class with regards to the reaction of cocoa to stress . This is supported by the findings of Djocgoue et al (2007) who reported that qualitative analysis of phenolics in leaves of cocoa showed a higher accumulation of the flavonoids (luteolin and apigenin derivatives) and some hydroxycinnamic acid derivatives. The significant negative correlation between metabolites (TPP and TF) and length of necrosis trait reflects the importance of the biochemical compounds in tolerance expression.…”
Section: Discussionsupporting
confidence: 81%
“…Among these flavonoids, flavan-3-ol units are a major class with regards to the reaction of cocoa to stress . This is supported by the findings of Djocgoue et al (2007) who reported that qualitative analysis of phenolics in leaves of cocoa showed a higher accumulation of the flavonoids (luteolin and apigenin derivatives) and some hydroxycinnamic acid derivatives. The significant negative correlation between metabolites (TPP and TF) and length of necrosis trait reflects the importance of the biochemical compounds in tolerance expression.…”
Section: Discussionsupporting
confidence: 81%
“…However, negative heterosis observed in hybrid genotypes could be explained by the epistatic effect of some genes which tend to mask genes controlling tolerance to P. megakarya. Similar results were also obtained by Djocgoue et al (2007) and Ondobo et al (2014) when leaves of T. cacao were inoculated with P. megakarya. Early studies of Mohammadi et al (2012) showed that, resistance to Septoria tritici blotch is controlled by additive, dominance and epistatic gene action, but the role of the dominant gene effect is greater than the others.…”
Section: Discussionsupporting
confidence: 75%
“…These leaf discs were placed with their abaxial surface upwards in side trays. On the other hand, six whole leaves of cocoa were set apart in a single tray and arranged according to the protocol described by Djocgoue et al (2007). These discs and whole leaves were all simultaneously inoculated with 10 µl of 10 6 zoospore ml -1 suspension of P. megakarya.…”
Section: Induced Resistance Assessmentmentioning
confidence: 99%
“…The extraction and quantitative measurement of the content of total phenolic compounds were performed as described by Djocgoue et al (2007) with modification. Total phenolic compounds were extracted twice using 80% methanol.…”
Section: Determination Of the Content Of Total Phenolic Compoundsmentioning
confidence: 99%